Importance of a Risk Stratification Strategy to Identify High-risk Patients Presenting With Cocaine-associated Acute Coronary Syndrome. Issue 3 (September 2018) - Sehatbakhsh, Samineh; Kushnir, Alexander; Furlan, Stefanie; Donath, Elie; Ghumman, Waqas; Chait, Robert
Abstract : Objective: Current guidelines recommend treating patients with cocaine-associated chest pain, unstable angina, or myocardial infarction similarly to patients with traditional acute coronary syndrome (ACS). Risk stratifying these patients could potentially reduce unnecessary procedures and improve resource utilization. Methods: This is a retrospective cross-sectional analysis of 258 patients presenting with cocaine-associated ACS who underwent cardiac catheterization in a community teaching hospital between 2006 and 2015. The primary outcome was the prevalence of acute obstructive coronary artery disease (CAD) requiring percutaneous coronary intervention and coronary artery bypass grafting compared with that of patients with normal coronary or nonobstructive disease. Results: Of the studied population, 36% had obstructive CAD requiring intervention and 64% were found to have normal coronaries or nonobstructive disease. Significant risk factors for obstructive CAD were older age, history of CAD, diabetes mellitus, dyslipidemia, ST-segment–elevation myocardial infarction, and troponin elevation. A logistic model was developed based on these variables, applied to the studied population, and was found to have 93% sensitivity in predicting the likelihood of obstructive CAD. Conclusions: Cardiac catheterization in patients presenting with cocaine-associated ACS may be overutilized. A predictive model based on clinical risk factors may help individualize patient care and reduce unnecessary invasive diagnostic interventions.